1991
DOI: 10.2105/ajph.81.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and abuse in random samples of physicians and medical students.

Abstract: BACKGROUND. This study sought to resolve conflicting views about whether physicians are especially prone to alcohol abuse. METHODS. Using an anonymous, mailed questionnaire on substance use, we surveyed 500 physicians, 510 pharmacists, and 974 of their students. The physicians and pharmacists were selected randomly from the state society's membership lists, and students selected were from local school lists. Follow-up surveys were sent to nonresponders at two-week intervals. RESULTS. The physicians and medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
14

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 42 publications
6
39
0
14
Order By: Relevance
“…When we compared our results with those of other studies investigating substance use in different populations of doctors, 19,20 we found the extremely low reported rate of alcohol abuse both surprising and rather difficult to accept. aim to modify the medical culture which pressurises doctors into believing that they should never be sick, or at least that they should never complain or seek help.…”
Section: Discussionmentioning
confidence: 57%
“…When we compared our results with those of other studies investigating substance use in different populations of doctors, 19,20 we found the extremely low reported rate of alcohol abuse both surprising and rather difficult to accept. aim to modify the medical culture which pressurises doctors into believing that they should never be sick, or at least that they should never complain or seek help.…”
Section: Discussionmentioning
confidence: 57%
“…Las escuelas de medicina no están ajenas a este fenómeno, existiendo numerosa bibliografía internacional que da cuenta de consumos de magnitud variable, generalmente alto [9][10][11][12][13][14][15][16][17][18][19][20][21] . En el caso del alcohol, se han descrito al estrés y las presiones académicas, elementos propios de la carrera de medicina, como factores que esgrimen los estudiantes para consumirlo 9,11,13,19 .…”
Section: N V E S T I G a C I ó Nunclassified
“…y el Reino Unido. El consumo de alcohol entre sus estudiantes de medicina es mayor, oscilando entre 86% y 95% [16][17][18][19][20] , y su intensidad de consumo en un día habitual también es superior 16,17,19 . Elementos culturales y religiosos pueden explicar esta diferencia entre países 9 , por lo que no nos deben conformar comparaciones favorables frente a paí-ses anglosajones.…”
Section: N V E S T I G a C I ó Nunclassified
See 2 more Smart Citations